2013
DOI: 10.1590/s1676-06032013000200035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on germination of four legumes from a forest-grassland mosaic in Southern Brazil

Abstract: Passage of a fire can break dormancy of the seeds of many plant species in fire-prone ecosystems. This response to fire is especially well known for the Fabaceae family, but has been poorly studied in Southern Brazil. We collected seeds of four Fabaceae species present in grasslands-forest mosaics of Southern Brazil: Mimosa bimucronata, Desmodium barbatum, Sesbania virgata and Collaea stenophylla. Seeds were exposed to different heat treatments (exposure to 60° and 80 °C for 5 minutes, to 100 °C for 2 minutes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Earlier studies found little evidence that germination could be enhanced by seed exposure to high temperatures (Overbeck et al 2006;Fidelis et al 2010b). However, recent studies (Silveira & Overbeck 2013) have demonstrated that heat exposure at 80ºC led to increased germination by a grassland legume, Desmodium barbatum.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Earlier studies found little evidence that germination could be enhanced by seed exposure to high temperatures (Overbeck et al 2006;Fidelis et al 2010b). However, recent studies (Silveira & Overbeck 2013) have demonstrated that heat exposure at 80ºC led to increased germination by a grassland legume, Desmodium barbatum.…”
mentioning
confidence: 98%
“…In fact, Bradstock & Auld (1995) registered temperatures from 0-3cm soil depth ranging from 60ºC to 120ºC. Moreover, we used temperatures similar to the ones used by Overbeck et al (2006) and Silveira & Overbeck (2013) in studies on seed germination of Brazilian subtropical grasslands. Therefore, we chose the range from 60ºC (which is usually measured in the upper layers of soils during fire) to 150ºC (extreme temperatures) to test our hypothesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing seeds of some Mimosa species to high temperatures greatly stimulated germination (Chauhan and Johnson 2009). Conversely, germination of M. bimucronata seeds decreased after a few minutes of pretreatment at 80 and 100°C (Silveira and Overbeck 2013). Therefore, conditions for seed coat break seem to vary among Mimosa species.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Reyes and Trabaud (2009) Núñez and Calvo (2000) also observed that high temperature did not increase the germination in Pinus halepensis and Pinus sylvestris. Silveira and Overbeck (2013) tested the seeds of Fabaceae species and the seeds were exposed to different heat treatments (exposure to 60° and 80 °C for 5 minutes, to 100 °C for two minutes). The effect of heat-shock treatments (60, 80, 100, 120 and 140 °C for five min) on the germination of 21 herbaceous species in Central Anatolian steppe was evaluated and it is suggested that the seeds of plant species in Central Anatolian steppes are resistant to low-intensity surface fires (Tavsanoglu et al 2015).…”
Section: Discussionmentioning
confidence: 99%